Evaluation of Internationally Accredited Study Programs through Learning Quality Audits in Maintaining the Quality of Education - Indrarini, Rachma; Prakoso, Albrian Fiky; Trisnawati, Novi; Yanthi, Merlyana Dwinda; Arifah, Ika Dyah Candra; Kusumawati, Nunik Dwi; Westermann, Alena (IKIP Widya Darma Surabaya, 2025)
Objective: This study evaluates internationally accredited study programs through a learning quality audit to ensure the sustainability of educational quality. Method: A qualitative descriptive approach was employed, collecting data through This study employs an audit method using the CIPP evaluation model (context, input, process, and product). Several stages carried out in the evaluation include Preparing the Evaluation Plan, Verifying Data, Processing and Analyzing Data, Providing Interpretation, and Drawing Conclusions. Results: The results indicate variations in compliance among study programs, where programs that have been accredited show better performance but still face challenges in curriculum restructuring, academic documentation, and international collaboration. Meanwhile, study programs that are in the process of accreditation have greater weaknesses, particularly related to evidence-based accreditation and follow-up mechanisms. This audit emphasizes the importance of continuous improvement, strengthening internationalization, and systematic documentation. Novelty: This research refers to two international accreditation monitoring simultaneously, namely AQAS and Acquin.